Retrospective Review of Bilateral Decompressive Craniectomy of 51 Patients after Severe Traumatic Head Injury (Bangladesh Journal of Neurosurgery, 2022)
Background: Decompressive craniectomy (DC) is one of the commonly used treatment modalities for refractory intracranial hypertension after severe traumatic brain injury.Objective: To assess the functional outcome following bilateral decompressive craniectomy (DC) in traumatic head injury based on Glasgow Outcome Scale (GOS).Materials and methods: This is a retrospective study conducted at Enam Medical College & Hospital, from January 2019- December 2020. Data of the patients who had undergone bilateral DC for severe traumatic head injury were reviewed from medical record files. Data were collected pre-designed data collection sheet. Data were analyzed using computer based program statistical package for social science (SPSS) for windows version 25.0 software.Results: This study shows maximum (56.9%) were 16-30 years. The average age was 29.70±14.78 years. Majority were male (94.1%) and only 5.9% were female. Road traffic accidents (RTA) were the most frequent causative event of traumatic injury. Most of the patients (88.2%) were hospital stay 1-5 days then 9.8% were 6-10 days and only 2% were >10 days. The average hospital stays were 3.26±2.43 days. Majority (60.7%) were good recovery, 13.7% were moderate disability, 5.9% were severe disability, 2% were persistent vegetative state and 13.7% were death at home.Conclusion: This study recommends a larger prospective study to assess the longterm functional outcome of bilateral decompressive craniectomy after severe traumatic head injury.Bang. J Neurosurgery 2022; 11(2): 89-93